Gary Cooper off camera: - Janis, Maria Cooper (Abrams, 1999)
Maria Cooper Janis' heartfelt book offers an unprecedented look at her father's private side, from his Montana boyhood and his Hollywood home life, to his friendships with Ernest Hemingway, Pablo Picasso and Jimmy Stewart